Compression-distraction reduction surgical verification and optimization to treat the basilar invagination and atlantoaxial dislocation: a finite element analysis. Issue 2 (December 2016) - Bo, Xuefeng; Wang, Weida; Chen, Zan; Liu, Zhicheng
Abstract Background Basilar invagination (BI) combined with atlantoaxial dislocation (AAD) leads to foramen magnum stenosis and medullary spinal cord compression, causing nerve dysfunction. The purpose of the surgery is to remove the bony compression at brainstem ventral side and fix the unstable spinal segment and make it fused stably. Occipital cervical internal fixation system that simultaneously reduces atlantoaxial horizontal and vertical dislocation are established. We propose here a new compression-distraction reduction (CDR) technique. We aimed to construct a congenital BI-AAD preoperative finite element model (FEM) to simulate the CDR technique for AAD reduction surgery. Methods Based on computed tomographic scans of patients' cervical vertebrae, a three-dimensional (3D) geometric model of the cervical spine (C0–C4) of congenital BI-AAD patients was established using Mimics13.1, Geomagic2012, and Space Claim14.0 softwares. The mechanical parameters of the tissues were assigned according to their material characteristics using ANSYS Workbench 14.0 software. A 3D FEM was established using the tetrahedral mesh method. The bending moment was loaded on C0. Physiological conditions—anteflexion, retroflexion, left and right flexion, left and right rotation—were simulated for preoperative verification. The occipital cervical fixation system FEM was established. The CDR technique was simulated to perform AAD reduction surgery. Data were obtained when the atlantoaxial horizontal and vertical dislocation reductions were verified postoperatively. Stress data for the two surgical schemes were analyzed, as was the reduction surgery optimization scheme for congenital BI-AAD patients with abnormal lateral atlantoaxial articulation ossification. Results Cervical spine (C0–C4) FEM of congenital BI-AAD patients was established. The CDR technique was simulated for AAD reduction. We obtained the mechanical data when the atlantoaxial horizontal and vertical dislocation reductions were satisfied for the two surgical schemes. Conclusions The CDR technique for AAD reduction was feasible and effective. We propose this reduction optimization scheme for patients with lateral atlantoaxial articulation due to abnormal ossification of congenital BI-AAD. We also provide a biomechanically theoretical basis for improving the reliability of pure posterior reduction surgery and simplifying surgery for complicated BI-AAD disease.